Application of low frequency ECT method in noncontact detection and visualization of CFRP material. (1st February 2017) - Cheng, Jun; Qiu, Jinhao; Ji, Hongli; Wang, Enrong; Takagi, Toshiyuki; Uchimoto, Tetsuya
Abstract: In view of low conductivity and thin layer structure of carbon fiber reinforced polymer (CFRP), the high frequency eddy current testing (HF-ECT) technique operating in the frequency range up to 100 MHz is considered to be better suited for this less conductive material. However, high frequency ECT method is more susceptible to various interference factors, causing many difficulties in the system construction and implementation. Concerning this issue, the feasibility of using low frequency ECT method for CFRP inspection was fully explored in this paper, and on this basis a high precision low frequency ECT system with the working frequency up to 250 kHz was developed. The system is mainly involving the small-size transmitter-receiver (T-R) type of probe, weak-signal extraction method using the lock-in amplifier and the C-scan imaging technique. The true skin depths of eddy current generated in unidirectional and orthogonal CFRP plates by small air-cored coil were calculated with 3D finite element simulation, thereby determining the high sensitivity of low frequency ECT for surface and near surface defects in CFRP. With the developed system, the direction of different fiber plies was successfully detected, and the location and size of different damages were also clearly visualized in the scan image. The proposed research can play a role of guiding the development of highly effective low frequency ECT method and detecting system for CFRP material.